Beam profile and pulse width assessment in an engineered D-shaped hollow-core photonic crystal fiber. (15th November 2021) - Saeedizadeh, Reza; Sabouri, Saeed Ghavami; Khorsandi, Alireza
Abstract: In this work, a theoretical model is discussed to investigate the performance of a core-engineered gas-filled hollow-core photonic crystal fiber (HC-PCF). To gain the shortest pulse width and the best beam quality at the output, the core geometry of the fiber is modified within four specific types referred to as type I to type IV fibers. It is found that, by using type III and type IV HC-PCF devices, a 5 ps laser pulse in the input can be respectively compressed to 18.5 fs and 13.7 fs at the output. It is found that, a 5-ps laser pulse in the input can be reduced to 18.5 fs and 13.7 fs if type III- and type IV of modified HC-PCF device are respectively used for compression. The structural similarity (SSIM) index is used to evaluate the quality of the beam cross-section that ultimately emerges from the end of the fiber. The results suggest that the highest SSIM value of 0.76 can be obtained if type III HC-PCF is employed for pulse compression.